Informasi Kesehatan melalui Leaflet dan Penyuluhan di Desa Kemingking Luar Kec. Taman Rajo - Mukhlis Sanuddin; Aldi Dwi Hernawan; Anisar Anisar; Chervia Oktariani; Veni Apriliya (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Kemingking Luar Village Taman Rajo District Muaro Jambi Regency is a village that has an area of 820,0000 hectares (hectares) and has a population of ± 483 people. The border of the village of Kemingking Luar is bordered by the village of Muaro Jambi. Problems in the village of Kemingking Luar namely rheumatism and hypertension, based on field surveys for hypertension and rheumatism in the Village of Kemingking Luar are still very bad because of the work of the majority of farmers. In addition, the survey results also show that family medicinal plants (TOGA) in Kemingking Luar Village have almost 70% already existed, only the use of TOGA is still lacking because people do not know the benefits and processing of TOGA. for self-medication and to be used as a product of economic value for the people of Kemingking Luar Village, and other problems that occur in Kemingking Luar Village, such as smoking habits, and the lack of community activities to lead a healthy life. Based on this data, students from the Real Work Lecture at Kemingking Luar Village provide counseling and skills to the community of Kemingking Luar Village such as Rheumatism, Gout, Blood Sugar, DAGUSIBU, and Blood Pressure counseling, correct treatment methods, and how to manage TOGA into a TOGA form. valuable and beneficial products for the surrounding community, and utilize TOGA.